Stepping to phase-perturbed metronome cues: multisensory advantage in movement synchrony but not correction - Wright, Rachel L.; Spurgeon, Laura C.; Elliott, Mark T. (Frontiers in Human Neuroscience, 2014)
Humans can synchronise movements with auditory beats or rhythms without apparent effort. This ability to entrain to the beat is considered automatic, such that any perturbations are corrected for, even if the perturbation was not consciously noted. Temporal correction of upper limb (e.g. finger tapping) and lower limb (e.g. stepping) movements to a phase perturbed auditory beat usually results in individuals being back in phase after just a few beats. When a metronome is presented in more than one sensory modality, a multisensory advantage is observed, with reduced temporal variability in finger tapping movements compared to unimodal conditions. Here, we investigate synchronisation of lower limb movements (stepping in place) to auditory, visual and combined auditory-visual metronome cues. In addition, we compare movement corrections to phase advance and phase delay perturbations in the metronome for the three sensory modality conditions. We hypothesised that, as with upper limb movements, there would be a multisensory advantage, with stepping variability being lowest in the bimodal condition. As such, we further expected correction to the phase perturbation to be quickest in the bimodal condition. Our results revealed lower variability in the asynchronies between foot strikes and the metronome beats in the bimodal condition, compared to unimodal conditions. However, while participants corrected substantially quicker to perturbations in auditory compared to visual metronomes, there was no multisensory advantage in the phase correction task – correction under the bimodal condition was almost identical to the auditory-only condition. On the whole, we noted that corrections in the stepping task were smaller than those previously reported for finger tapping studies. We conclude that temporal corrections are not only affected by the reliability of the sensory information, but also the complexity of the movement itself.